Exercise rehabilitation following intensive care unit discharge for recovery from critical illness: executive summary of a Cochrane Collaboration systematic review. Issue 5 (16th September 2016) - Connolly, Bronwen; Salisbury, Lisa; O'Neill, Brenda; Geneen, Louise; Douiri, Abdel; Grocott, Michael P. W.; Hart, Nicholas; Walsh, Timothy S.; Blackwood, Bronagh
Abstract: Skeletal muscle wasting and weakness are major complications of critical illness and underlie the profound physical and functional impairments experienced by survivors after discharge from the intensive care unit (ICU). Exercise‐based rehabilitation has been shown to be beneficial when delivered during ICU admission. This review aimed to determine the effectiveness of exercise rehabilitation initiated after ICU discharge on primary outcomes of functional exercise capacity and health‐related quality of life. We sought randomized controlled trials, quasi‐randomized controlled trials, and controlled clinical trials comparing an exercise intervention commenced after ICU discharge vs. any other intervention or a control or 'usual care' programme in adult survivors of critical illness. Cochrane Central Register of Controlled Trials, Medical Literature Analysis and Retrieval System Online (MEDLINE), Excerpta Medica Database, and Cumulative Index to Nursing and Allied Health Literature databases were searched up to February 2015. Dual, independent screening of results, data extraction, and quality appraisal were performed. We included six trials involving 483 patients. Overall quality of evidence for both outcomes was very low. All studies evaluated functional exercise capacity, with three reporting positive effects in favour of the intervention. Only two studies evaluated health‐related quality of life and neither reported differences between intervention and control groups. Meta‐analyses of data were precluded due to variation in study design, types of interventions, and selection and reporting of outcome measurements. We were unable to determine an overall effect on functional exercise capacity or health‐related quality of life of interventions initiated after ICU discharge for survivors of critical illness. Findings from ongoing studies are awaited. Future studies need to address methodological aspects of study design and conduct to enhance rigour, quality, and synthesis.